Pengembangan Bisnis Sektor Pertanian Melalui Pemanfaatan Data Produksi Bawang Merah di Provinsi Nusa Tenggara Barat - Widia; Ranita Balaningrum; Sri Wahyuni; Karina Utami; Herie Saksono (Penerbit Indocamp, 2024)
This study aims to develop a business model for the shallot farming sector in West Nusa Tenggara (NTB) Province, which is carried out by utilizing production data for the last 10 years. Shallot growth in NTB was studied using a quantitative approach, identifying four different growth patterns between regions. The research results show that shallot production in NTB has experienced significant growth, but there are disparities between areas. To increase production and distribution efficiency, shallot crop development strategies need to pay attention to annual production data, product innovation, resource processing, and eco-tourism. Improvements in governance and trading systems are also needed to achieve better price stability. Therefore, it is necessary to meet the needs of technology, and agricultural infrastructure and increase the capacity of farmers to increase overall productivity. This study concludes that business development in the shallot farming sector in NTB requires a comprehensive approach through various strategies to achieve sustainable and equitable growth throughout the region. The development of the shallot business in NTB should ideally include increasing added value, product diversification, marketing optimization, implementing appropriate business models, innovation, market expansion, and establishing farmer partnership patterns. Technological innovation, evidence-based policies, and strengthening value chains were highlighted as important steps in increasing shallot production sustainably in NTB.